2021
DOI: 10.3855/jidc.15030
|View full text |Cite
|
Sign up to set email alerts
|

Infectious diseases screening approach among refugees: results from a single-center study

Abstract: Introduction: Our aim was to evaluate a screening program, with active case-finding and treatment for active tuberculosis (TB), latent tuberculosis infection (LTBI), blood-borne viruses (BBV), and sexually transmitted diseases (STDs) among refugees living in facility centers. Methodology: We collected data on refugees arriving to our attention in migrant centers in Sardinia, Italy. Socio-demographical data, anamnesis, and clinical features were collected. TST Mantoux was conducted, and X-ray chest (XRC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
2
7
1
Order By: Relevance
“…The lack of symptoms is an important barrier to screening, as shown by Hamdiui, Steenbergen ( 42 ). Filling knowledge and awareness gaps through education, can increase the perceived risk, perceived disease severity and perceived healthcare needs, which are predictors for screening ( 41 , 43 , 73 , 77 ).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of symptoms is an important barrier to screening, as shown by Hamdiui, Steenbergen ( 42 ). Filling knowledge and awareness gaps through education, can increase the perceived risk, perceived disease severity and perceived healthcare needs, which are predictors for screening ( 41 , 43 , 73 , 77 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to a study based on data collected in migrant centres in Sardinia, Italy, 40.7% of the 81 people investigated had scabies, 49.4% had a positive Mantoux test, 50% had a positive hepatitis B virus serology, 12.3% had anal or genital lesions due to syphilis, and one person died of MDR-TB. 24 Although, as we have shown above, the current circumstances of migration are different, these data point out that there is a great need for coordination of medical surveillance in these situations. Under the current conditions of Ukrainian national health care, the country was not prepared to quickly identify the spread of COVID-19 and to respond effectively in the early stages of the pandemic.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies suggest that a higher prevalence is found among not-recently-arrived migrants. Two studies conducted among African asylum seekers report similar prevalence (Fiore et al, 2019, 1.1% and Donisi et al, 2015, 1.9%) [37,38]. At the same time, two studies addressing undocumented migrants report a higher prevalence, ranging from 2.2% to 3.3% [39,40].…”
Section: Epidemiologymentioning
confidence: 88%